2008
DOI: 10.3368/jhr.43.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Peer Effects in Academic Cheating

Abstract: a b s t r a c tUsing self-reported academic cheating from the classes of 1959 through 2002 at the three major United States military service academies (Air Force, Army, and Navy), we measure how peer cheating influences individual cheating behavior. We find higher levels of peer cheating result in a substantially increased probability that an individual will cheat. One additional college student who cheated in high school drives approximately 0.33 to 0.47 additional college students to cheat. One additional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 32 publications
6
64
0
Order By: Relevance
“…Previous research has indicated that cheating norms are incredibly important to students' decisions to cheat (Carrell et al, 2008;McCabe & Trevino, 1997;McCabe et al, 2001). One of the most direct ways that counternormative pressure can be applied is through the direct censure of peers.…”
Section: Cheating Preventionmentioning
confidence: 98%
“…Previous research has indicated that cheating norms are incredibly important to students' decisions to cheat (Carrell et al, 2008;McCabe & Trevino, 1997;McCabe et al, 2001). One of the most direct ways that counternormative pressure can be applied is through the direct censure of peers.…”
Section: Cheating Preventionmentioning
confidence: 98%
“…Similarly, Van Yperen, Hamstra, and van der Klauw (2011) show that goal setting can increase cheating. 10 Focusing on cheating in peer settings without monetary or task interdependencies, a number of studies based on field data show that own cheating behavior positively depends on perceptions or expectations of others' cheating behavior, that is the acceptability of cheating or the norm for cheating (Beekun and Westerman 2012;Carrell, Malmstrom, and West 2008;Deshpande and Joseph 2009;Ichino and Maggi 2000;Jones and Kavanagh 1996;Megehee and Spake 2008;O'Fallon and Butterfield 2012;Ostermaier and Uhl 2017;Pierce and Snyder 2008). 10 Focusing on cheating in peer settings without monetary or task interdependencies, a number of studies based on field data show that own cheating behavior positively depends on perceptions or expectations of others' cheating behavior, that is the acceptability of cheating or the norm for cheating (Beekun and Westerman 2012;Carrell, Malmstrom, and West 2008;Deshpande and Joseph 2009;Ichino and Maggi 2000;Jones and Kavanagh 1996;Megehee and Spake 2008;O'Fallon and Butterfield 2012;Ostermaier and Uhl 2017;Pierce and Snyder 2008).…”
Section: Related Literaturementioning
confidence: 99%
“…Students seem to feel that the likelihood of being caught is minimal and that they are justified in doing what everyone else is doing (Selwyn 2008). Carrell et al (2008) concentrated on peer influence as a contributing factor in US military academies. While they acknowledge that the military setting might differ considerably from that of US universities, the study does confirm that peer cheating has a considerable effect on individual cheating.…”
Section: Reasons For Plagiarismmentioning
confidence: 99%